Java Hibernate cookbook: over 50 recipes to help you build dynamic and powerful real-time Java Hibernate applications - Prajapati, Yogesh; Ranapariya, Vishal (PACKT Publishing, 2015)
Hibernate is a database independent technology, so the same code will work for all databases. It helps a Java developer write a query by mapping Java bean to database tables and help create tuned queries that boost performance. Even with limited SQL knowledge one can easily perform database operations. This makes the development faster and more accurate than JDBC. Hibernate supports useful features like connection pooling, caching, and inheritance etc. This book will provide a useful hands-on guide to Hibernate to accomplish the development of a real-time Hibernate application. We will start with the basics of Hibernate, which include setting up Hibernate – the pre-requisites and multiple ways of configuring Hibernate using Java. We will then dive deep into the fundamentals of Hibernate such as SessionFactory, session, criteria, working with objects and criteria. This will help a developer have a better understanding of how Hibernate works and what needs to be done to run a Hibernate application. Moving on, we will learn how to work with annotations, associations and collections. In the final chapters, we will see explore querying, advanced Hibernate concepts and integration with other frameworks.